Evaluation of different methods of environmental enrichment to control anxiety in dogs undergoing hemilaminectomy after acute intervertebral disc extrusion: a randomized double-blinded study - Pennington, Ellery; Springer, Cary; Albright, Julia; Castel, Aude (Frontiers in Veterinary Science, 2023)
Objective: The goal of this randomized double-blinded placebo-controlled study was to evaluate the effect of environmental enrichment (EE) on post-operative pain and anxiety in dogs following hemilaminectomy for acute intervertebral disc extrusion (IVDE). Methods: Twenty healthy client-owned dogs undergoing a hemilaminectomy for IVDE with the same immediate post-operative analgesia protocol were randomly assigned to either the EE or standard (SE) post-operative environment. Recovery was in an intensive care room (SE) or a separate quiet room (EE) equipped with white noise and classical music. EE dogs were also exposed to dog-appeasing-pheromones, essential oil scents, positive human interactions and had meals provided through food toys. A blinded evaluator assessed all dogs using the modified Glasgow Composite Pain Scale (mGCPS) on presentation and at several time points post-operatively. A rescue injection of the opioid methadone was given for a mGCPS score ≥ 5/20. Dogs received the antidepressant trazodone when anxious behaviors (5mg/kg) were observed. The mGPS scores, the latencies to receive the first methadone and trazodone doses and to eat the first meal, the number of methadone and trazodone doses and number of meals ingested in the first 24- and 48-hours post-surgery, were compared with Wilcoxon tests and Benjamini-Holchberg correction for false discovery rate was applied. Results: Although median mGPS scores did not differ between groups, EE dogs (n=6) received trazodone sooner (p=0.019), fewer methadone injections at 24h (p=0.043) and ate more 48h post-surgery (p=0.007) than SE dogs (n=10). EE and anti-anxiety medications could be beneficial to improve the wellbeing of dogs post-operatively.